Influence of lingual plate fracture pattern on remodelling site during the healing process of sagittal split ramus osteotomy. Issue 5 (May 2022) - Moroi, A.; Takayama, A.; Baba, N.; Iguchi, R.; Yoshizawa, K.; Ueki, K.
Abstract: The purpose of this study was to investigate whether differences in the pattern of the lingual plate split in sagittal split ramus osteotomy (SSRO) affect the remodelling of the split site. Sixty-one patients with mandibular prognathism (122 sides) underwent SSRO. Computed tomography (CT) was performed at 1 week and 1 year after SSRO. Bone splits were classified according to the lingual split scale (LSS) and the lateral bone cut end (LBCE) by evaluating CT images at 1 week. The remodelling at the split sites was evaluated by superimposing the CT images obtained at 1 week and 1 year. Regarding the LSS pattern, significant differences were observed in the distance between anteroposterior ramus points ( P = 0.033) and the ramus area in the axial image ( P = 0.011). The LBCE pattern also showed a significant difference in the distance between anteroposterior ramus points ( P = 0.043). In conclusion, the differences in the lingual plate split and ramus cut end of the SSRO influence the postoperative remodelling in the anteroposterior region of the split site.